(3EOGQI SdGSd GdJhQjOs - (3YHO GdSJGQ(B, (3eMeO GdYdjs; (3Ndjd GHQGgje GdcfYGfj(B, s ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2009)
(3GdJRhjO hSdGSd GdJhQjO, SdSdI GdJhQjO hNOeI GdRHhf, GdbjeI hcda GdJRhjO, GddhLSJc heWGHbI GdJhQjO eY GdWdH, GddhLSJc hGOGQI GdTQGA hGNJjGQ hJbjje GdehQOjf, GdCOhGJ GdeSGfOI aj GOGQI SdSdI GdJhQjO, GOGQI SdGSd GdJhQjO aj Xd GdYhdeI, GddhLSJc heOI GdJhQjO, GOGQI SdSdI GdJhQjO hGdTQGcI, GddhLSJc hJbjje hbjGS GdeNRhf, feGPL GdeNRhf GdGbJUGOj, GfhGY GdWdH hGfXeI GdTQGA, JNWjW GdeJWdHGJ GdeGOjI, fXGe GdLOhdI GdahQjI, GOGQI Gdfbd, JcfhdhLjG GdeYdheGJ hGOGQI SdSdI GdJhQjOs
(3HHdjhZQGajG(B: (3U(B.535s
Keywords: (3GOGQI GdCYeGds; (3GdGOGQIs; (3GdJRhjOs; (3GdJShjbs